CD4 count evaluation in HIV-TB co infection before and after anti-tubercular treatment - S, Kavya; K, Anuradha; D, Venkatesha (International Journal of Research in Medical Sciences, 2017)
Background:The global impact of Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) co-infection is one of the major public health challenge. India has a very high burden of TB according to the WHO. A decrease in CD4 counts in HIV-TB co-infection leads to an increase in morbidity and mortality. Methods:Information regarding the duration of HIV, type of TB, CD4 counts before and after ATT and any associated Opportunistic Infections (OIs) were collected from the records of 100 patients with HIV-TB co-infection who attended ART centre for a period of one year. The collected data was statistically analyzed. Results: In the study group, 35 had Pulmonary Tuberculosis (PTB) and 65 had Extra Pulmonary Tuberculosis (EPTB), 40 had OIs. Mean CD4 count prior to ATT in PTB was 197 (7-940), EPTB 192 (13-683) and with OIs 129 (7-288). After completion in PTB was 300, EPTB 302 and 252 in OIs. Least CD4 count of 121 was observed in patients above 50yrs and after completion it was 133. Incidence of both EPTB and PTB was higher in males 66.2% and 62.9%, and in the age group of 31-50 yrs 50.8% and 60% (Cell counts expressed in cells/µl.). Conclusion:In our study, we found that there was significant recovery of CD4 cells following ATT. Difference in CD4 counts among patients with PTB and EPTB was not significant. There was remarkable reduction of CD4 counts in patients who had other OIs and the recovery after ATT was also marginal.